A Comparative Analysis of Numerals in Uzbek, English, and Korean - Furkat kizi, Furkatova Madina (Journal of Innovation in Education and Social Research, 2025)
This research explores how numbers function in three linguistically diverse languages: Uzbek from the Turkic family, English from Germanic origins, and Korean from the Koreanic group. The investigation analyzes how counting words—both cardinal numbers and ordinal numbers—are constructed, their historical roots, and how they function within sentences. By comparing these languages side by side, the study uncovers patterns that appear across all human languages alongside unique features specific to each tongue. Results show that although each language uses a base-ten counting system, their complexity varies considerably. These insights prove valuable for teaching languages, professional translation work, and studying how different cultures process numerical concepts.